Penerapan Media Video Tutorial pada Elemen Pembuatan Pola Dasar Badan terhadap Hasil Belajar Siswa di Kelas X Tata Busana SMK Negeri 3 Kediri - Izzalinta Tika Gunawan; Marniati Marniati; Ratna Suhartini; Urip Wahyuningsih (Journal on Education, 2024)
The objectives of this research are to determine 1) the implementation of learning on the elements of making basic patterns of the female body using video tutorial media, 2) student responses with the application of video tutorial media on the elements of making basic patterns of women's bodies, 3) the influence of video tutorial media on student learning outcomes. This research used a quantitative descriptive research method with research subjects of 34 students of Class X Fashion Design 1 SMK Negeri 3 Kediri.The research results show that: 1) The use of video tutorial media in implementing the learning process is categorized as very good so that it is very effective in teaching students; 2) The results of the student response questionnaire show that the average student response is interested in using video tutorials as a learning medium; 3) The learning outcomes of students who use video tutorial media increase significantly so that they are included in the complete category. The findings of this research are able to help students understand the material so as to achieve the completeness criteria in the KKTP (Learning Achievement Criteria). Apart from that, the application of video media can not only be applied in schools but students can apply video tutorials anywhere and anytime, therefore video tutorial media is said to be very good for application in learning.